Antibiotic Resistance Acquisition in the First Week of Life - Barraud, Olivier; Peyre, Marianne; Couvé-Deacon, Elodie; Chainier, Delphine; Bahans, Claire; Guigonis, Vincent; Ploy, Marie-Cécile; Bedu, Antoine; Garnier, Fabien (Frontiers in Microbiology, 2018)
Objectives: The fetus is considered sterile but recent studies have suggested that gut colonization could start before birth. Scarce data are available for the acquisition of resistant Gram-negative bacteria (GNB) during the first days of life. Several studies have shown that integrons play a major role in antibiotic resistance acquisition. In this work, we studied the dynamics of human intestinal acquisition of GNB and integrons during the first days of life. Methods: Meconium was collected at birth and a stool sample before hospital discharge (day 2 or 3) on 185 term neonates. GNB were searched by culture on each sample and class 1, 2 and 3 integrons from each GNB or directly from samples. Eight risk factors for integron and GNB acquisition were studied. Results: We isolated 228 GNB, 46 from meconium and the remainder from stools. No link was found between GNB isolation and antibiotic exposure during delivery, but antibiotic exposure during labor significantly selected blaTEM-positive amoxicillin-resistant Enterobacteria. Two-thirds of GNB were antibiotic-susceptible and most of the resistant isolates were acquired after birth. Integrons were detected in 18 of the 228 GNB isolates from 3 meconium and 20 stools. Antibiotic administration during delivery and vaginal carriage of S. agalactiae appeared as risk factors for integron acquisition. Conclusions: GNB and integrons are mostly acquired after birth during the first days of life even if for some term neonates, meconium was not sterile. Antibiotic administration during delivery is a major risk for integron acquisition and for selection of amoxicillin-resistant Enterobacteria.